FMS Corrective Intervention Improves FMS Composite Score and 1-Mile Run Time, without Concurrent Change in Hip Extension Strength, Vertical Jump or T-Shuttle Run Time, in Recreational Runners - Dallam, George; Hostetter, Karen; McFadden, Michael; Bowan, Daniel; Pickeril, Marie; McClaran, Steve (Journal of Sports Research, 2019)
The purpose of this research was to examine the effect of an intervention designed to improve functional movement as determined by Functional Movement Screen ™ (FMS) composite scores, one mile run time, standing isometric hip extension strength, agility T-Test time, and vertical jump in recreational runners (N=12, 7 males and 5 females; Mean Age = 49.08±15.87 yrs.; and mean weekly run volume = 15.96±21.21 miles), while normal running training load was maintained. We employed a two group (Control and Treatment) randomized experimental design. The treatment group (n=6) completed a 6 week intervention using the standard corrective methodology advocated by the FMS organization in combination with their normal run training, while the control group (n=6) continued their normal run training without additional intervention. We found a significant interaction between group and pre/post measure with a large effect sizes demonstrating improvement in the treatment group for the both the 1 mile run time (F = 5.45, p=0.042, Ɲp2= 0.353) and the FMS composite score (F = 10.55, p=0.009, Ɲp2= 0.513). There were no other significant interactions or meaningful effect sizes for any other dependent variable. This study supports the concept that a 6 week standard FMS intervention can result in concurrent improvements in both FMS composite score and 1 mile running performance without a concurrent change in running training load, isometric hip extension strength, vertical jump performance or t-shuttle times, in recreational runners.